COPING STRATEGY PADA KONDISI DARURAT BENCANA: PEMBELAJARAN DARI MASYARAKAT BANTUL MENGHADAPI GEMPA - Deny Hidayati (Jurnal Kependudukan Indonesia, 2012)
The 2006 Yogya earthquake had a great impact on the total number of victims and loss of property. During the emergency condition, the community had to struggle by itself to survive and to reduce further disaster impacts. This paper discusses the coping strategy of the survival community in the District of Bantul, the Province of DI Yogyakarta, especially during the earthquake and a few days after the disaster before relief from the government and other donors arrived in the earthquake locations. Based on the result of LIPI qualitative research in the Project of Multidisiplinary Hazard Reduction from Earthquakes and Volcanoes in Indonesia, this paper highlights the important role of community institutions as social capital in reducing pressures that suddenly appeared due to the earthquakes. The community carried out some emergency efforts by managing the local wisdom based on their daily lives and culture. Individuals within the community held together in small groups of neighbours, neighbourhoods, compounds or hamlets helping each other andcarrying out cooperative activities based on gender roles. They faced the difficult conditions and provided for their basic needs together in order to survive and continue their lives after the disaster. They also provided the basic needs priority for vulnerabe groups and other members of the community who needed more for their survival.Key Words: coping strategy, local wisdom, community, emergency condition,earthquake disaster.